The Use of Mobile Assisted Language Learning Among Professional Workers - Fatimah, Anggun Nadia; Hadinayu, Atmaradhifa; Dewi, Alfina Rahmah (STKIP AGAMA HINDU SINGARAJA, 2025)
This research aims to discuss more deeply the utilization of Mobile Assisted Language Learning (MALL) technology in a foreign language learning experience specific to seven participants from the professional working class, including CEO, Trainee Coach, Finance Staff, and University Staff. The concept of Uses and Gratifications (UGT) and Media Affordances will be used as a guide to deepen the analysis of the data obtained using a qualitative approach. Data was collected through in-depth interviews with seven workers from various sectors who are actively or have used language learning apps. The results show that the use of MALL apps by working professionals is driven by several factors such as satisfaction (technology, entertainment, social, utilitarian, and content), interactive features and ease of access, and purpose of use. The purpose of use is not only for professional needs (improvement of work/academic skills), but also used for personal satisfaction in learning a foreign language